Perancangan Prototype Aplikasi Laikanggu dengan Pendekatan User Centered Design Menggunakan Figma: The Design of the Laikanggu Application Prototype with a User-Centred Design Approach Using Figma - Ikhuzain Maftuh Aksa; Alfiah Fajriani; Muhammad Akbar Yasin (ITScience (Information Technology and Science), 2025)
Effective and efficient healthcare services are among the main challenges faced by various healthcare facilities, including RSUD Konawe Utara. To address this challenge, an innovative solution in the form of the Laikanggu application (Layanan Integrasi Kesehatan Terpadu Tepat Guna) has been developed. This application aims to integrate various healthcare services into a single, easily accessible digital platform. The purpose of this study is to ensure that the development of the application is based on the actual needs of the users through a User-Centered Design (UCD) approach. The research methodology includes a literature review, interviews with healthcare professionals, and usability testing to gather insights into users' needs and experiences directly. The prototype design was carried out using Figma, a design tool that facilitates the creation of interactive and intuitive system visualizations. Usability evaluations of the application were conducted using the System Usability Scale (SUS), which provides a quantitative measure of user comfort and satisfaction levels. The results of the study indicate that the Laikanggu application prototype has a high level of usability and is considered effective in improving healthcare service efficiency at RSUD Konawe Utara. The application’s design, developed using the User-Centered Design (UCD) approach, has proven to meet the users' needs, thus enhancing service effectiveness and providing a better experience for both healthcare providers and patients. In conclusion, the Laikanggu application has the potential to become an innovative solution for improving digital healthcare services at RSUD Konawe Utara and holds the opportunity for adoption by other hospitals in the future.